Harvesting of microalgae via submerged membranes: flux, fouling and its reversibility - Elcik, Harun; Cakmakci, Mehmet (TECHNO-PRESS, 2017)
The purpose of this study was to investigate membrane fouling caused by microalgal cells in submerged membrane systems consisting of polymeric and ceramic microfiltration membranes. In this study, one polymeric (flat-sheet, pore size: 0.2 mu m) and two ceramic (flat- sheet, pore size: 0.2 mu m and cylindrical, pore size: 1 mu m) membranes were used. Physical cleaning was performed with water and air to determine the potential for reversible and irreversible membrane fouling. The study results showed that substantial irreversible membrane fouling (after four filtration cycles, irreversible fouling degree 27% (cleaning with water) and 38% (cleaning with air)) occurs in the polymeric membrane. In cleaning studies performed using water and air on ceramic membranes, it was observed that compressed air was more effective (recovery rate: 87-91%) for membrane cleaning. The harvesting performance of the membranes was examined through critical flux experiments. The critical flux values for polymeric membrane with a pore size of 0.20 mu m and ceramic membranes with a pore size of 0.20 mu m and 1 mu m were <= 95 L/m(2) hour, <= 70 L/m(2) hour and <= 55 L/m(2) hour, respectively. It was determined that critical flux varies depending on the membrane material and the pore size. To obtain more information on membrane fouling caused by microalgal cells, the characterization of the fouled polymeric membrane was performed. This study concluded that ceramic membranes with a pore size of 0.2(-1) mu m in the submerged membrane system could be efficiently used for microalgae harvesting by cleaning the membrane with compressed air at regular intervals.
Keywords: membrane; microalgae; critical flux; fouling; reversibility; EXTRACELLULAR ORGANIC-MATTER; ULTRAFILTRATION UF MEMBRANE; CROSS-FLOW MICROFILTRATION; FILTRATION PERFORMANCE; PORE-SIZE; BIOMASS; BIOFUELS; ALGAE; CELLS; EOM; Engineering; Water Resources